(untitled) (Universal International Scientific Journal, 2026)
his paper examines how higher education reforms reshape the competitive environment of universities in Uzbekistan and why strategic management becomes decisive for sustaining and strengthening competitive advantages. The study conceptualizes universities’ competitive advantages as a combination of strategic resources and capabilities (human capital, research and innovation capacity, educational quality, partnerships, governance effectiveness, and digital transformation readiness) that create stakeholder value and improve institutional positioning. Using a conceptual-analytical approach based on the synthesis of international and national research, the paper develops a strategic framework that links reform drivers to strategic choices and measurable outcomes. The results highlight key managerial priorities: aligning institutional strategy with reform requirements, strengthening quality assurance systems, investing in academic staff development, expanding external partnerships, and introducing performance-based governance tools. The proposed framework can be applied by university management to diagnose strategic gaps, select development priorities, and design organizational and economic mechanisms that enhance competitiveness during reform